2017
DOI: 10.1371/journal.pone.0168977
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Volumetric versus Manual Measurement in Disseminated Testicular Cancer; No Difference in Assessment between Non-Radiologists and Genitourinary Radiologist

Abstract: BackgroundThe aim of this study was to assess the feasibility and reproducibility of semi-automatic volumetric measurement of retroperitoneal lymph node metastases in testicular cancer (TC) patients treated with chemotherapy versus the standardized manual measurements based on RECIST criteria.Methods21 TC patients with retroperitoneal lymph node metastases of testicular cancer were studied with a CT scan of chest and abdomen before and after cisplatin based chemotherapy. Three readers, a surgical resident, a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This technique has been used as a “gold standard” to test against semi-automated segmenting in multiple volumetric studies and has been validated in volumetric assessment of testicular cancer metastases to lymph nodes. 15–18 The current study found that MS was the only strategy tested which demonstrated no significant difference between the average true and measured volumes irrespective of tumor shape. MS allowed for precise contouring of tumor borders but still had only moderate ICC between true and measured volume and moderate interobserver variability.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This technique has been used as a “gold standard” to test against semi-automated segmenting in multiple volumetric studies and has been validated in volumetric assessment of testicular cancer metastases to lymph nodes. 15–18 The current study found that MS was the only strategy tested which demonstrated no significant difference between the average true and measured volumes irrespective of tumor shape. MS allowed for precise contouring of tumor borders but still had only moderate ICC between true and measured volume and moderate interobserver variability.…”
Section: Discussionmentioning
confidence: 54%
“…The SA strategy uses software tools to perform volumetric measurement by manually selecting lesions in the axial and coronal plane followed by linear interpolation to create a 3D view. 15 Observers then visually assess the segmentation and make adjustments if the contour of the lesion is unsatisfactory. After segmentation, the software automatically generates and displays a volume in milliliters.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have shown that computer-aided volumetric tumour assessment is a promising technique in improving inter-observer variability, both with detection and diagnosis of lesions. 24,25,26…”
Section: Discussionmentioning
confidence: 99%
“…Automatic measurements allow for a more objective approach and can easily incorporate growth in multiple dimensions. Volumetric analysis has been explored to improve the assessment of tumor burden [39,42,45,[125][126][127].…”
Section: Discussionmentioning
confidence: 99%